How Are Banks Doing on Sustainable Finance? - Świeszczak, Marika (Journal of Finance and Financial Law, 2020)
In recent years, the banking sector has started to prioritize sustainable development, recognizing the growing benefits of sustainable investment. However, they e ncounter many obstacles on the road, among others, the time horizon, waiting for regulatory proposals, and a lack of understanding of the potential effects of climate change. To strengthen its sustainability policy, the ESMA decided to harmonize transparency rules that should have a significant impact on the entire banking sector. The purpose of the article is to organize basic definitions related to the sustainable development policy, to show the role of finance in the whole process, to present important changes in the regulation, and to approximate current changes in the field of sustainable development in the banking sector.